DISTORSI KAPASITAS PERDAGANGAN INTER-REGIONAL IMT-GT Kasus Provinsi Terpilih di Sumatera Indonesia - Avianto, Benito Rio; Koestoer, Raldi Hendro (Universitas Muhammdaiyah Surakarta, 2010)
The objective of the paper was to understand the impact of sub regional economic cooperation, known as the Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT), on trade sector in Indonesia. The approach of research based on export macro information by provinces and commodities. The method used in the analytical framework was a fixed effect method. The regional study covered Nanggroe Aceh Darussalam, North Sumatera, West Sumatera, and Riau provinces, and the commodities involved CPO, coffee and rubber, with 1990-2008 data series. Based on pooled regression, there was a significant impact on export from the four provinces to Malaysia and Thailand for all based years. One might focus on commodity level that, in fact, CPO was the only one commodity that had a significant impact within the IMTGT region. In addition, Thai Bath and Malaysian Ringgit, with respect to GDP for both countries, had significant influenced on export, especially after the IMT-GT endorsed.